Respostas

A melhor resposta!
2014-05-18T12:16:04-03:00
x² - 7x + 6 = 0
a = 1
b = -7
c = 6
       Δ = b² - 4ac
       Δ = (-7)² - 4 . 1 . 6
       Δ = 49 - 24
       Δ = 25
                x = - b ± √Δ / 2a
                x = - (-7) ± √25 / 2 . 1
                x' = 7 - 5 / 2           x'' = 7 + 5 / 2 
                x' = 2 / 2                x'' = 12 / 2
                x' = 1                    x'' = 6

x² - 8x + 15 = 0
a = 1
b = -8
c = 15
       Δ = (-8)² - 4 . 1 . 15
       Δ = 64 - 60
       Δ = 4
                x = - (-8) ± √4 / 2 . 1
                x' = 8 - 2 / 2           x'' = 8 + 2 / 2      
                x' = 6 / 2                x'' = 10 / 2
                x' = 3                    x'' = 5

x² + 10x + 25 = 0
       Δ = 10² - 4 . 1 . 25
       Δ = 100 - 100
       Δ = 0
                x = - 10 ± √0 / 2 . 1
                x' = - 10 - 0 / 2       x'' = - 10 + 0 / 2  
                x' = -10 / 2             x'' = -10 / 2
                x' = -5                   x'' = -5

3x² + 4x + 1 = 0
       
Δ = 4² - 4 . 3 . 1
       Δ = 16 - 12
       Δ = 4
               x = - 4 ± √4 / 2 . 3
               x' = - 4 - 2 / 6          x'' = - 4 + 2 / 6  
               x' = -6 / 6                x'' = - 2 / 6 (simplifcando ambos por 2)
               x' = -1                    x'' = -1 / 3

Espero ter ajudado. Valeu!
1 5 1
vlw brother, me ajudou mt !
De nada, amigo!
2014-05-18T12:21:24-03:00
X²-7x+6=0:
a=1,b=-7,c=6
Δ=b²-4ac
Δ=-7²-4·1·6
Δ=49-24
Δ=25.
x=-b+ou-√Δ sobre 2a
x=-(-7) +-√25 sobre 2a
x=7+- 5 sobre 2
x'=7+5 sobre 2=12sobre 2=6
x''=7-5 sobre 2=2 sobre 2=1


x²-8x+15=0
a=1,b=-8,c=15
Δ=b²-4ac
Δ=-8²-4·1·15
Δ=64-60
Δ=4.
x=-b+ou-√Δ sobre 2
x=-(-8)+-√4 sobre 2
x=8+- 2 sobre 2
x'=8+2 sobre 2=10 sobre 2=5
x''=8-2 sobre 2=6 sobre 2=3